International market selection using fuzzy weighing and monte carlo simulation [Selekcja rynków międzynarodowych z wykorzystaniem logiki rozmytej i symulacji monte carlo] (2017)
This article aims to develop a methodology for the international market selection (IMS), using fuzzy logic for the uncertainty of the variables in the market evaluation. Therefore, several procedures are proposed, including market pre-selection, criteria definition, criteria weighting, data collection, data variability and a market evaluation model. Through Monte Carlo simulation, the market evaluation model measures the stability of international markets for exporting when criteria are fuzzy. A case study for the export of frozen beef from Colombia validates the methodology. The proposed approach helps to improve the exporting performance, and it is applicable for small and medium enterprises because the model uses free access data sources, and the algorithms of the market evaluation model can be performed in spreadsheets. © 2017, Czestochowa University of Technology. All rights reserved.